Design of Thin Steel Roof Battens Subject to Pull-through Failures - Mayooran, S.; Mahen, M. (University of Jaffna, 2022)
The use of thin steel roof battens for roof structures has been increased notably around the world. However, the occurrences of more intense and frequent storms due to climate changes have been a major cause of significant roof failures. Recent wind damage studies have highlighted that such severe roof failures occur predominantly in the form of localized pull through failures of thin steel roof battens. Although recent research studies have developed suitable design methods, they have not considered very thin steel roof battens (<0.5 mm). Hence this research is aimed to assess the suitability of current design equations for the design of very thin steel roof battens subject to pull-through failures. A series of pull-through failure tests of roof battens was conducted for this purpose under simulated static wind uplift load and this paper presents the details and results from this study.
Keywords: Thin steel roof batten; High wind; Uplift load; Pull-through failure; Design equation